A platform for modular assembly and feeding of micro-organoids on standard Petri dishes - Nebuloni, F; Morgan, J; Walsh, EJ; Cook, PR (Company of Biologists, 2023)
Organoids grow in vitro to reproduce structures and functions of corresponding organs in vivo. As diffusion delivers nutrients over only ∼200 µm, refreshing flows through organoids are required to avoid necrosis at their cores; achieving this is a central challenge in the field. Our general aim is to develop a platform for culturing micro-organoids fed by appropriate flows that is accessible to bioscientists. As organs develop from layers of several cell types, our strategy is to seed different cells in thin modules (i.e. extra-cellular matrices in stronger scaffolds) in standard Petri dishes, stack modules in the required order, and overlay an immiscible fluorocarbon (FC40) to prevent evaporation. As FC40 is denser than medium, one might expect medium to float on FC40, but interfacial forces can be stronger than buoyancy ones; then, stacks remain attached to the bottom of dishes. After manually pipetting medium into the base of stacks, refreshing upward flows occur automatically (without the need for external pumps), driven mainly by differences in hydrostatic pressure. Proof-of-concept experiments show that such flows support clonal growth of human embryonic kidney cells at expected rates, even though cells may lie hundreds of microns away from surrounding fluid walls of the two immiscible liquids.